2019
DOI: 10.1016/j.ebiom.2019.08.001
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA let-7-TGFBR3 signalling regulates cardiomyocyte apoptosis after infarction

Abstract: Background Myocardial infarction (MI) is a life-threatening disease, often leading to heart failure. Defining therapeutic targets at an early time point is important to prevent heart failure. Methods MicroRNA screening was performed at early time points after MI using paired samples isolated from the infarcted and remote myocardium of pigs. We also examined the microRNA expression in plasma of MI patients and pigs. For mechanistic studies, AAV9-mediated microRNA knockdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…Cardiomyocyte apoptosis is considered a significant event during the development of cardiomyopathy. let-7 has been shown to target TGF-3β and regulate cardiomyocyte apoptosis after MI [149]. Bioinformatic predictions have shown several genes, such as TBX5, FOXP1, HAND1, AKT2, and PPARGC1A, which are related to cardiac development, to be targets of different let-7s (let-7a/7d/7e/7f ) [150].…”
Section: Let-7's Protein Regulators and Their Role In Stroke And Other Cardiovascularmentioning
confidence: 99%
“…Cardiomyocyte apoptosis is considered a significant event during the development of cardiomyopathy. let-7 has been shown to target TGF-3β and regulate cardiomyocyte apoptosis after MI [149]. Bioinformatic predictions have shown several genes, such as TBX5, FOXP1, HAND1, AKT2, and PPARGC1A, which are related to cardiac development, to be targets of different let-7s (let-7a/7d/7e/7f ) [150].…”
Section: Let-7's Protein Regulators and Their Role In Stroke And Other Cardiovascularmentioning
confidence: 99%
“…let-7a downregulated the expression of its target Calmodulin (CaM) protein, that together with Ca 2+ induces the hypertrophic genes transcription (147). let-7a was found downregulated in myocardium of pigs after MI and also in plasma of humans and pigs after MI (148). In this study a let-7a overexpression was shown to be cardiac protective via inhibition of TGFBR3-p38 MAPK signalling pathways, that regulates cardiomyocyte apoptosis (148).…”
Section: Let-7 A/bmentioning
confidence: 65%
“…let-7a was found to be downregulated in the myocardium of pigs after MI and also in the plasma of humans and pigs after MI ( 148 ). In this study, a let-7a overexpression was shown to be cardiac protective via inhibition of TGFBR3-p38 MAPK signaling pathways that regulate cardiomyocyte apoptosis ( 148 ).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, these two DElncRNAs affected TGFBR3 expression by co-regulating the miR-27a-3p sponge via bioinformatics prediction. TGFBR3 expression is significantly upregulated in patients after myocardial infarction and may serve as a therapeutic target and biomarker for myocardial damage by activating p38 MAPK to induce cardiomyocyte apoptosis ( Chu et al, 2011 ; Chen et al, 2019 ). Moreover, it has been found that lncRNA SOX2-OT exacerbates hypoxia-induced cardiomyocyte injury by regulating the miR-27a-3p/TGFβR1 axis ( Yang and Lin, 2020 ).…”
Section: Discussionmentioning
confidence: 99%